1966
DOI: 10.1098/rsta.1966.0041
|View full text |Cite
|
Sign up to set email alerts
|

A discussion on deformation of solids by the impact of liquids, and its relation to rain damage in aircraft and missiles, to blade erosion in steam turbines, and to cavitation erosion - Rain erosion properties of materials

Abstract: A rotating arm apparatus capable of circumferential speeds up to 475 m/s (Mach 1.4) has been used to make quantitative measurements of the velocity and angle dependence of ram erosion for a wide range of materials. It has been possible to relate the mechanical properties of some materials with their rain erosion resistance. The behaviour of the drops during impact has been studied by high speed photography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Reduction of storage modulus of coating is beneficial for the erosion resistance Recovery of material after impact: short time, quick recovery of materials following impact is important for erosion resistance …”
Section: Mechanisms Of Leading Edge Erosion Of Wind Turbine Bladesmentioning
confidence: 99%
“…Reduction of storage modulus of coating is beneficial for the erosion resistance Recovery of material after impact: short time, quick recovery of materials following impact is important for erosion resistance …”
Section: Mechanisms Of Leading Edge Erosion Of Wind Turbine Bladesmentioning
confidence: 99%
“…Apart from this complexity in simulating rain itself due to size, shape, and velocity of raindrops, the modelling of the rain as an erosive phenomenon is still lacking the proper solutions. The studies to find models of the rain as erosive phenomenon have been carried out mainly using traditionally two different approaches, ie, the approaches have been considering the impact force or the energy transmitted …”
Section: Rain Erosion In Blade Leading Edgementioning
confidence: 99%
“…Early studies have shown that erosive wear resistance is proportional to material toughness, hence ultra-high-molecular-weight polyethylene (UHMWPE) erodes more slowly than polyester resin [68]. As can be seen from equation (11.19) the dependence of wear rate on impact velocity is extreme.…”
Section: Erosive Wear By Liquidmentioning
confidence: 99%